Performance Dependence of (I-V) and (C-V) for Solar Cells on Environmental Conditions (JOURNAL OF ADVANCES IN PHYSICS, 2018)
The present paper is a trial to shed further light on the dependence performance of mono-crystalline silicon solar cell (photovoltaic cell) on the environmental conditions. In this concern, the static (I-V) and dynamic (C-V) characteristics measurement were studied in details under the effect of illumination type, intensity and wavelength, as well temperature on the physical and electrical parameters of solar cell. The dependence of cell parameters- extracted from (I-V) characteristic curves- open-circuit voltage (Voc), short-circuit current (Isc), fill-factor (FF), conversion efficiency (Î·) as well the series -and shunt-resistances (Rs and Rsh), on the intensity has been investigated for a wide illumination intensity range 1.0 - 70 mW/cm2. It was observed that, for illumination levels higher than 10 klux, the values of Voc, Rsh, FF and efficiency were shown to be saturated. Isc was shown to be increased linearly, while Rs decreased exponentially as a function of illumination level. On the other hand, considering the dynamic characteristics (C-V), a detailed study was carried out for solar cells biased on both the forward - and reverse modes at frequency range of 20 kHz - 140 kHz and different illumination - levels. From which, the barrier potential (Vbi) and doping (charge carrier) concentration (Na) were determined. Besides, the influence of temperature within the range from 30 up to 110 oC on both the static and dynamic characteristics was tested. From which, it is clear that Voc, maximum powers (Pmax), FF, Î· of the sample were shown to be temperature decreasing functions. Moreover, Isc has a feeble increasing temperature coefficient. Finally, the solar cell capacitance (C) and dissipation factor (D) rise with rising temperature in both bias voltage conditions, while, impedance (Z), quality factor (Q), and phase angle (Ï†) reduce with rising temperature.